NOD1 promotes leukocyte clearance and limits inflammation in female mice during obesity‐associated acute lung injury - Rodrigo Rodrigues e Lacerda; Nicole G. Barra; Han Fang; Gabriel Forato Anhê; Jonathan D. Schertzer (Physiological Reports)
Abstract Obesity is associated with metabolic inflammation, which includes changes to innate immune responses relevant to acute lung injury. NOD1 is a cytosolic pattern recognition receptor involved in sensing bacterial peptidoglycan and has been linked to metabolic inflammation. However, its role in obesity‐associated acute lung injury, especially in females, remains unclear. Here, we investigated the impact of NOD1 deficiency on pulmonary inflammation in female mice subjected to a high‐fat diet and lipopolysaccharide‐induced acute lung injury. Compared to wild‐type controls, obese Nod1−/− mice showed reduced leukocyte and neutrophil numbers in the bronchoalveolar lavage (BAL), but increased BAL levels of TNF‐α, IL‐1β, IL‐6, IL‐17A, and IL‐22, suggesting impaired neutrophil clearance. In the lung tissue, NOD1 deficiency during obesity led to elevated neutrophil accumulation, increased myeloperoxidase activity, reduced CD163+ macrophages, and enhanced β‐galactosidase activity. Gene expression analysis revealed upregulation of chemokines, adhesion molecules, and inflammasome components, alongside downregulation of M2 polarization markers. Additionally, obese Nod1−/− mice showed higher NF‐κB and ERK1/2 activation and lower p38 phosphorylation. These findings indicate that NOD1 regulates leukocyte dynamics, inflammation, and macrophage function in the obese lung. We identify NOD1 as a key protective modulator of pulmonary immune responses during acute lung injury under metabolic stress.